Answer:
-1is your answer to the question
Answer:
ab - bc = 6
Step-by-step explanation:
COMPUTATION:
ab - bc = ?
(2 x -3) - (-3 x 4) = ?
(-6) - (-3 x 4) = ?
(-6) - (-12) = ?
-6 + 12 = 6
Hope this helps!
The "rule" being described here is nothing more than the input/output of a mathematical function.
For every input 'x' value supplied, you only need to subtract three to it. For every input 'y' value, you only need to add four to it.
Example: I'll use variable 'm' to represent this function. Variable 'p' will represent the current input point.
m(p) = p[x - 3, y + 4] = p[-7 - 3, 0 + 4] = p[-10, 4]. 'p[]" is just the point.
I tried my best hope that help!
Answer:
Step-by-step explanation:
Eliminate answer 4 immediately, because (4)(3) is not 7.
Look at answer 2: 7x + 3x = 10x, which does not match the middle term 12x in the original polynomial. Eliminate answer 2.
Look at answer 1: 1x + 21x = 22x, which does not match the middle term of the original polynomial. Eliminate answer 1.
All quadratics have solutions. Let's apply the quadratic formula to 3x^2 + 12x + 7: Here a = 3, b = 12 and c = 7, so that the discriminant b²-4ac is
12²-4(3)(7), or 144 - 84, or 60. Being positive, this tells us that the given poly has two real, unequal roots:
-12 ± √60 -12 + 2√15 -12 - 2√15
x = ----------------- = ------------------- and x = --------------------
3 3 3
Normally, if c is a root, then x - c is a factor.
If we try this here, however, the resulting factors do not at all match any of your answer choices.
Don't be offended...but please ensure you have copied this problem down correctly.
Answer:
Possibly 3.
Step-by-step explanation:
A consecutive odd number that adds up to 39 and is the smallest (not including 1) is 3.
13, 3's equals to 39.